Planning to catalyze the counter magnet area: a case of Gwalior West - Shrivastava, Prashant (SPA Bhopal, 2018)
Cities promise to provide employments, good education, engagements of entertainment, fast mobility, physical comforts, diversity of culture and sense of purpose and esteem. Lured by all or any of these, flocks of people migrate to urban areas from sub-urban areas and villages. Urban population has grown at a rapid pace of 17 percent in 1951 to 28 percent in 2001 and shall touch 41 percent by 2030. The advances of technological and industrial world have exaggerated the glory of urban world even further. The polarization of population in cities has lead to increased densities there and due to this, enormous pressure is laid on the infrastructure, resources and environment of the cities. Our mega cities are more susceptible to this problem. Delhi, Mumbai and Kolkata are overloaded with enormous population from villages, towns, suburbs across India. The densities of these cities are proving threat to health-hygiene, safety, food availability and posing challenges to urban planners, administrators and common man. In order to combat this future threat, National Capital Region Planning Board (NCRPB), New Delhi, thought of developing Counter Magnet Areas in distant cities through an act in 1985. These Counter Magnet Areas are required to function for a dual purpose of intercepting the migratory flows to NCR and secondly, to become the centers of regional growth and achieve balanced pattern of urbanization. The five CMAs selected were Gwalior, Bareli, Kota, Hissar and Patiala. In these 30 years though, 1988 to 2018, the CMAs do not seem to have performed. This study intends to go deep into this viewpoint ,specially for the case of Gwalior , to find valid causes in master plan for its non- performanceand come with alternative strategic ideas to keep the CMA Gwalior on track ; in other words – Planning to catalyze the Counter Magnet Areas, A Case of Gwalior West.
Keywords: MURP (Master of Urban and Regional Planning); Counter Magnet Area; Gwalior; NCRPB; urbanization; migrate